Study of deep levels in the Mg2Si grown by vertical Bridgeman method. (1st May 2023) - Fukushima, Kouki; Mizunuma, Naoki; Uematsu, Tatsuya; Shimizu, Kyoko; Ota, Takehiro; Tsunoda, Isao; Yoneoka, Masashi; Udono, Haruhiko; Takakura, Kenichiro
Abstract: The electrical characteristics of a Mg2 Si p–n junction diode was investigated. The n-Mg2 Si substrate was grown by using the vertical-Bridgeman method. A p–n junction was fabricated by the thermal diffusion of Ag as an acceptor. The reverse current of the Au/Ag electrode diode was larger than that of the Ag electrode diode. The trap levels in the n-Mg2 Si bulk were investigated using deep-level transient spectroscopy. The magnitude of DLTS signal of E1 with the Au/Ag electrode diode was larger than that for the signals at the other trap levels. The E1 level corresponds to an Au-related trap that diffuses via thermal annealing during the alloying process. The open-circuit-voltage-decay study suggests the existence of a minority-carrier trap in n-Mg2 Si. The minority-carrier lifetime was shorter for Au/Ag electrode diodes. Therefore, Au may be involved in the formation of minority-carrier traps, as well as in the formation of majority-carrier traps.